MODELING OF ELECTRONIC OPEN EDUCATIONAL RESOURCES - Nina V. Komleva (Открытое образование (Москва))
The article is devoted to modeling the process of creating open educational resources (OER). The technology of processing of the content presented in this paper provides solutions for the creation of competitive highquality e-learning courses, placed in an open information environment. The tools are analyzed in detail to create a virtual environment OER. The algorithm of the decision making process on the processing of contentbased neuro-fuzzy.